Effect of a dedicated mitral heart team compared to a general heart team on survival: a retrospective, comparative, non-randomized interventional cohort study based on prospectively registered data. (30th March 2021) - Sardari Nia, Peyman; Olsthoorn, Jules R; Heuts, Samuel; van Kuijk, Sander M J; Vainer, Jindrich; Streukens, Sebastian; Schalla, Simon; Segers, Patrique; Barenbrug, Paul; Crijns, Harry J G M; Maessen, Jos G
Abstract:  : OBJECTIVES: Although in both the US and European guidelines the 'heart team approach' is a class I recommendation, supporting evidence is still lacking. Therefore, we sought to provide comparative survival data of patients with mitral valve disease referred to the general and the dedicated heart team. METHODS: In this retrospective cohort, patients evaluated for mitral valve disease by a general heart team (2009–2014) and a dedicated mitral valve heart team (2014–2018) were included. Decision-making was recorded prospectively in heart team electronic forms. The end point was overall survival from decision of the heart team. RESULTS: In total, 1145 patients were included of whom 641 (56%) were discussed by dedicated heart team and 504 (44%) by general heart team. At 5 years, survival probability was 0.74 [95% confidence interval (CI) 0.68–0.79] for the dedicated heart team group compared to 0.70 (95% CI 0.66–0.74, P  = 0.040) for the general heart team. Relative risk of mortality adjusted for EuroSCORE II, treatment groups (surgical, transcatheter and non-intervention), mitral valve pathology (degenerative, functional, rheumatic and others) and 13 other baseline characteristics for patients in the dedicated heart team was 29% lower [hazard ratio (HR) 0.71, 95% CI 0.54–0.95; P  = 0.019] than for the general heart team. The adjusted relative risk of mortality was 61% lower for patients following the advice of the heart team (HR 0.39, 95% CI 0.25–0.62; P  < 0.001) and 43% lower for patients following the advice of the general heart team (HR 0.57, 95% CI 0.37–0.87; P  = 0.010) compared to those who did not follow the advice of the heart team. CONCLUSIONS: In this retrospective cohort, patients treated for mitral valve disease based on a dedicated heart team decision have significantly higher survival independent of the allocated treatment, mitral valve pathology and baseline characteristics.